Culture dimensions and application of IFRSs in the banking industry - Lopes, A. I. (WSEAS Transactions on Business and Economics, 2016)
Using European and Asian banks, this paper investigates how differences in culture in different countries can be related with Loan loss provisions (LLP) based on the Hofstede’s theory. The effect of the application of International Financial Reporting Standards (IFRSs) on the amount of LLP recognized in financial statements published by Banks is also under analysis. Findings suggest that some culture dimensions play a role when analyzing risk factors, but not in all situations. When scores based on characteristics and behavior attributable to national culture are conflicting, the influence of culture on loan loss provisions is rejected. However, the application of IFRSs (vs local GAAP) has an important role, changing the power of national culture to influence the levels of LLP in countries where the scores of culture dimensions are according to the theory, and mitigating that influence when the scores are conflicting, moderating the amount of LLP that Banks should report regardless of culture behavior.